(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aimed to demonstrate the impact of job rotation through (job design, job development, systems and procedures) on administrative creativity in the banks under study. The study relied on the descriptive approach to describe and analyze the research variables based on the collected primary data. Through the researcher’s review of previous studies and literature, and in order to test the hypotheses, the researcher dumped the primary data into a database that was analyzed using SPSS version 20. The most important results of the study were as follows: There is a strong correlation between job design and administrative creativity, as the coefficient of determination reached 0.921, which indicates that 92.1% of the changes in administrative creativity follow changes in job design, and there is a strong correlation between job development and administrative creativity, where the value of the correlation coefficient is 0.928, and the coefficient of determination is 0.862 , which indicates that 86.2% of the changes in managerial creativity follow changes in job development, which means that there is an impact of job development on managerial creativity. The study’s most important recommendations were as follows The necessity of looking at job rotation as an important policy and strategy by paying attention to job design and development and paying attention to systems and procedures because this enables the worker to carry out his work in a renewed and developed manner, and enables him to present new suggestions and ideas, enhances his ability to predict problems related to his work, and enables him to participate in his superiors in Determine the goals of the unit I work in